HUMANIORA DIGITAL UNTUK WARISAN BUDAYA (KRITIS, 2022)
Digital Humanities (DH) is a conceptual framework, an approach, and a method that has shaped contemporary studies and management of cultural heritage. The DH method started in the 1960s-70s among linguistic and literary studies scholars who applied DH perspective to carry out research on textual materials. The development of visual graphic and internet technologies have enabled the DH to be applied for the studies on cultural heritage materials. DH has changed social science and humanities paradigm. When most social science and humanistic work remains as individual and limited projects, the DH approach uses computation to expand the social science and humanities work to involve more media platforms and reach a wider subject matters or audiences. The DH opens the social science and humanities research to diverse audio- visual forms, no longer limiting social science and humanities work to textual form. In Indonesia, DH approach and method has not yet been applied in cultural heritage studies and management. Digitizing heritage is a new initiative that has just started in the last decade. However, the digitizing work has not gone beyond simply recording and documentation practice. In so doing, the digitizing initiative in Indonesia has not resorted to the DH’s most important contribution as a critical paradigm in heritage research.